Nonsuicidal Self-injury: A Systematic Review - Cipriano, Annarosa; Cella, Stefania; Cotrufo, Paolo (Frontiers in Psychology, 2017)
Objective: Nonsuicidal self-injury (NSSI) refers to the intentional self-inflicted destruction of body tissue without suicidal intention and for purposes not socially sanctioned. Our paper presents an up-to-date overview on nonsuicidal, self-injurious behaviors. Method: In accordance with PRISMA guidelines, a systematic literature search was conducted across two databases, PubMed and PsycARTICLES, regarding the main features of NSSI with a focus on epidemiological and etiologic data, diagnostic criteria, and functions. All English articles, published between 1998 and 2016, were considered, and screened against a priori inclusion/exclusion criteria. The search terms include: self-harm, self-injury, NSSI, epidemiology, comorbidity, gender, functions and DSM. We also examined the references of the retrieved articles. Results: NSSI is most common among adolescents and young adults, and the age of onset is reported to occur between 12 and 14 years. Comorbidity with borderline personality disorder (BPD) and eating disorders is often reported. DSM-5 includes NSSI as a condition requiring further study. This review gives an overview of the prevalence rates (7.5–46.5% adolescents, 38.9% university students, 4–23% adults) and main causes that appear to stem from childhood trauma, comorbidity with many other disorders and several functions of NSSI, and the potential independence of a NSSI disorder. Conclusion: Over the years, interest in NSSI grew to such an extent that an ongoing debate was instigated on whether NSSI should be considered as a diagnosis in its own right and given its own category. This paper provides an up-to-date overview on self-injury, what is known about it and what remains to be done. Clearly, our understanding of the main issues of NSSI has increased in last two decades. However, future researches is needed to examine the developmental trajectories, cultural backgrounds and shed light on the risk factors and functions as well as clarify its role as an independent diagnostic entity.